Policy Analysis of Collection of Land and Building Tax in Pematang Serai Village, Langkat Regency - Dito Aditia Darma Nasution; Galih Supraja; Annisa Fajariah Damanik (Universitas 17 Agustus 1945 Semarang, 2023)
This study raises the phenomenon of the policy of collecting Rural Land and Building Tax in Pematang Serai Village, Langkat Regency. The reason for this research was carried out because of the facts and data which show that in 2018-2021 tax realization for Pematang Serai Village has not reached the target every year. Some of the things that become a problem in this study are the many phenomena of tax objects that are not in accordance with the number of taxpayers that must be paid by the community, low public awareness, ineffective mechanisms, and limited payment media in Pematang Serai Village. Researchers view and analyze the development of PBB collection in Pematang Serai Village comprehensively so that they can provide constructive suggestions. In this study, researchers used implementation theory by applying the George C Edward III implementation model. This theory uses 4 indicators, namely: communication, disposition, resources, and bureaucratic structure. This study uses qualitative research methods with data collection techniques through observation, interviews, and documentation. Meanwhile, data analysis techniques used data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the PBB collection policy in Pematang Serai Village, Langkat Regency is still not optimal, so it is recommended that the government pay attention to the land and building tax management policy that has been implemented so far so that it will be able to increase land and building tax revenue. It is also recommended through research results that in order to increase the effectiveness of Land and Building Tax revenue, the government should improve office facilities and infrastructure to support work activities, in addition to providing guidance to collectors and imposing sanctions on taxpayers regarding the importance of Land and Building Tax, because with the Land and Building Tax it will be used to finance regional development.